Measurement of Spiritual Care Competence: A Literature Review - Wahyu Kurniasih; Dodi Wijaya; Anisah Ardiana (GLOBAL HEALTH SCIENCE GROUP, 2025)
The measurement of spiritual care competence is a crucial aspect of healthcare, particularly in nursing and mental health settings, where holistic care is emphasized to achieve well-being for patients, especially those with terminal conditions. However, determining the appropriate instrument to measure spiritual care competence in nurses is not an easy task. This study aims to identify the most suitable instruments for measuring spiritual care competence in nurses in Indonesia. The method used in this study is a literature review. The keywords used to search for relevant journals are